MITIGASI RISIKO RANTAI PASOK PADA UMKM MEBEL KAYU JATI MENGGUNAKAN METODE HOUSE OF RISK DAN SIMPLE MULTI-ATTRIBUTE RATING TECHNIQUE - Widyastuti, Khoirunisa Wahyu; Sofiana, Amanda; Aulia Imran, Rani (nter of Execellence (COE) ICT Infrastructure, Smart Manufacture and Digital Supply Chain, 2025)
This research aims to identify various risks present in the supply chain activities of teak wood furniture production at Jati Bahagya Gallery and to establish priorities for mitigation actions against these risks. The approach used includes the Supply Chain Operation Reference (SCOR) model to map the supply chain flow, the House of Risk (HOR) method to evaluate risk events and their causes (risk event and risk agent), and the Simple Multi-Attribute Rating Technique (SMART) method to establish risk mitigation priorities. The mapping results revealed 26 risk events and 28 risk causes spread across five main processes: plan, source, make, deliver, and return. Through Aggregate Risk Potential (ARP) analysis and a Pareto diagram, three main risk causes were identified: increased operational costs, low wood quality, and production locations scattered across various cities. Eight risk mitigation proposals were obtained and then organized and prioritized based on a combination of Effectiveness to Difficulty (ETD) values and the results of the SMART method calculation. The final result of this research produces a prioritized sequence of mitigation actions that can be implemented by the company, which is expected to serve as a foundation for improving the supply chain system and enhancing operational efficiency.